Augmented reality development using multimedia development life cycle (MDLC) method in learning media - Solehatin, Solehatin; Aslamiyah, Sulaibatul; Pertiwi, Dwika Ananda Agustina; Santosa, Kevin (Journal of Soft Computing Exploration, 2023)
Practical classroom learning in the multimedia department requires props, where props range from damage. To address this need, learning media are made by applying Augmented Reality. Learning media presents actual images without holding and seeing the objects in real terms so that there is no damage to the props. This research was conducted to create learning media for students of SMK Negeri 1 Banyuwangi majoring in multimedia as an Android-based teaching aid. Stages of research using the development method in the form of Multimedia Model Life Cycle (MDLC). The concept stage analyzes and applies the Augmented Reality (AR) method, the design stage performs application planning according to the needs of learning media. The data collection stage conducted interviews with teachers and students while the stages of making learning media used Blender, Unity and Visual Studio software. At the trial stage of the application by making a guidebook, it was carried out for students at SMK Negeri 1 Banyuwangi. For the stages of distributing learning media using the Likert scale method through distributing questionnaires. The results of the application trials and questionnaire distribution, the responses of students about learning media, the results show the interpretation of respondents by combining a value of 72.22%, which means students accept this learning media. The results of this research can create learning media for multimedia majors that can reduce the risk of damage to props and provide cool and fun learning media.